Luminescent multifunctional hybrids obtained by grafting of ruthenium complexes on mesoporous silica - Sábio, Rafael Miguel [UNESP]; Gressier, Marie; Caiut, José Maurício A.; Menu, Marie-Joëlle; Ribeiro, Sidney J.L. [UNESP] (Elsevier, 2016)
This work evaluates the luminescent properties of new hybrids obtained by covalent grafting of ruthenium complexes on mesoporous silica particles. Spray pyrolysis afforded the mesoporous silica particles in one step; two different types of structure-directing agents were employed. Scanning and transmission electron microscopy (SEM and TEM, respectively) analyses confirmed that the particles had spherical morphology and ordered hexagonal mesoporosity (2 and 5 nm), which justified the high surface area up to 1420 m2 g-1 measured by Brunauer-Emmett-Teller (BET) surface area analysis. Covalent grafting of silylated ruthenium(II) complexes [Ru(bpy)21]Cl2 and [Ru(bpy)22]Cl2 on the mesoporous particles gave monolayered hybrids, characterized by fourier transform infrared spectroscopy (FTIR), TEM, and photoluminescence. Results highlighted the formation of new luminescent platforms containing an estimated 0.11 mmol of ruthenium(II) complex per gram of silica, which corresponded to 0.09 ruthenium(II) complex nm-2 of silica.
Keywords: Hybrid; Luminescence; Porous materials; Silylated complexes; Spray pyrolysis